HYGIENIC ANALYSIS OF THE DEPENDENCE OF THE QUALITY OF LIFE IN PATIENTS WITH PSORIASIS ON MORBIDITY INDICATORS - N.Zh. Ermatov; U.A. Tashkenbayeva; D.B. Khazhiev; E.Kh. Turakulov (Central Asian Journal of Medicine, 2023)
The purpose of the study. Assessment of risk factors for the development of the disease in patients with psoriasis. Materials and methods of research. To determine and compare risk factors in the study, a ratio of 1:1 (69:69) of the case (patients) and control (healthy) groups was taken and the gradation of risk factors affecting health indicators was analyzed. Risk factors were divided into external and internal, as well as depending on groups of vitamins and foods. According to the results obtained, among the external factors, the greatest value of the odds ratio was revealed with mechanical exposure–OSH (9.3), when using tobacco products, OR was equal to (5.7), when drinking alcohol, OSH was (5.4), when taking certain medications, OR was (4.9). Among the internal risk factors for the development of the disease, the greatest value of the odds ratio was revealed in the presence of obesity - OR 6,7, with an increase in blood pressure - OR 6,6, and with mental experiences - OR 4,2. The third group of risk factors consisted of various vitamin deficiencies, while the OR with cyanocabolamine deficiency as a risk factor was 6.4, with insufficient retinol OSH was equal to 5.7, with thiamine deficiency, OR was 4.7. Among the foods that are a risk factor for psoriasis, the OSH with excessive consumption of red pepper was 4.9, fried and fatty foods – OR - 4.5, tomatoes and eggplants, sweets and confectionery – OSH - 4.4.